Widespread Pain Is Associated with Increased Risk of No Clinical Improvement After TKA in Women - Vina, Ernest R. (Clin Orthop Relat Res, 2020)
BACKGROUND: When conservative treatments do not work, TKA may be the best option for patients with knee osteoarthritis, although a relatively large proportion of individuals do not have clinically important improvement after TKA. Evidence also suggests that women are less likely to benefit from TKA than men, but the reasons are unclear. Widespread pain disproportionately affects women and has been associated with worse outcomes after joint arthroplasty, yet it is unknown if the effect of widespread pain on TKA outcomes differs by patient gender. QUESTIONS/PURPOSES: (1) Does the association between widespread pain and no clinically important improvement in osteoarthritis-related pain and disability 2 years after TKA differ between men and women? (2) Does the use of pain medications 2 years after TKA differ between those with widespread pain and those without widespread pain before surgery? METHODS: Osteoarthritis Initiative (https://nda.nih.gov/oai/) study participants were followed annually from March 2005 until October 2015. Participants who underwent TKA up to the 7-year follow-up visit with pain/disability assessment at the protocol-planned visit before TKA and at the second planned annual visit after surgery were included in the analysis. Among 4796 study participants, 391 had a confirmed TKA, including 315 with pain/disability assessment at the protocol-planned visit before TKA. Overall, 95% of participants (298) had the required follow-up assessment; 5% (17) did not have follow-up data. Widespread pain was defined based on the modified American College of Rheumatology criteria. Symptoms were assessed using the WOMAC pain (range 0 to 20; higher score, more pain) and disability (range 0 to 68; higher score, more disability) scores, and the Knee Injury and Osteoarthritis Outcome Score for pain (range 0 to 100; higher score, less pain). Improvements in pain and disability were classified based on improvement from established clinically important differences (decrease in WOMAC pain ≥ 1.5; decrease in WOMAC disability ≥ 6.0; increase in Knee Injury and Osteoarthritis Outcome Score for pain ≥ 9). At baseline, more women presented with widespread pain than men (45% [84 of 184] versus 32% [36 of 114]). Probability and the relative risk (RR) of no clinically important improvement were estimated using a logistic regression analysis in which participants with widespread pain and those without were compared. The analyses were done for men and women separately, then adjusted for depression and baseline outcome scores. RESULTS: Among women, preoperative widespread pain was associated with an increased risk of no clinically important improvement 2 years after TKA, based on WOMAC pain scores (13.5% versus 4.6%; RR 2.93 [95% CI 1.18 to 7.30]; p = 0.02) and the Knee Injury and Osteoarthritis Outcome Score for pain (16.5% versus 4.9%; RR 3.39 [95% CI 1.34 to 8.59]; p = 0.02). Given the lower and upper limits of the confidence intervals, our data are compatible with a broad range of disparate associations between widespread pain and lack of clinically important improvement in WOMAC pain scores (RR 0.77 [95% CI 0.22 to 2.70]; p = 0.68) and the Knee Injury and Osteoarthritis Outcome Score for pain (RR 1.37 [95% CI 0.47 to 4.00]; p = 0.57) among men, as well as clinically important improvement in WOMAC disability scores among men (RR 0.72 [95% CI 0.20 to 2.55]; p = 0.61) and women (RR 1.98 [95% CI 0.92 to 4.26]; p = 0.08). Participants presenting with widespread pain before TKA were more likely than those without widespread pain to use medication for symptoms of knee osteoarthritis most days for at least 1 month 2 years after TKA (51% [61 of 120] versus 32% [57 of 178]; mean difference, 18.8 [95% CI 7.3 to 30.1]; p < 0.01). CONCLUSIONS: Widespread pain before TKA was associated with an increased risk of no clinically important improvement in knee pain 2 years postoperatively among women. Because of the small number of men with widespread pain in the sample, the results for men were inconclusive. In clinical practice, screening TKA candidates for widespread pain may be useful, and expectations of surgical outcomes may need to be tempered if patients have a concurrent diagnosis of widespread pain. Future studies should include more men with widespread pain and investigate if treatment of widespread pain before or concurrent with TKA surgery may improve surgical outcomes. LEVEL OF EVIDENCE: Level III, therapeutic study.